Artificial intelligence and human–robot technologies in sports: A systematic literature review - Indrayogi Indrayogi; Davi Sofyan; Riza Sukma Fauzi; Uray Gustian (Universitas Sriwijaya, 2026)
Research Problems: The rapid advancement of robotics and artificial intelligence (AI) has accelerated the integration of Human–Robot Interaction (HRI) technologies into sports training and performance analysis. However, existing research remains fragmented across diverse technological domains, limiting a comprehensive understanding of HRI's contributions to athlete development. Research Objectives: This study aimed to systematically review and synthesize the current evidence on the application of HRI in sports, focusing on its roles in performance enhancement, injury prevention, and training optimization. Methods: A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Literature was retrieved from the Scopus database using predefined search strategies, yielding 158 records. After duplicate removal, screening, and eligibility assessment, 20 studies published between 2015 and 2026 met the inclusion criteria and were included in the final analysis. Results: The findings demonstrate that HRI technologies, including robotic training systems, wearable sensors, artificial intelligence, computer vision, and intelligent monitoring systems, significantly improve movement analysis, deliver personalised feedback, and facilitate adaptive training programs. Among the identified research themes, performance enhancement was the most extensively investigated, followed by training optimization and injury prevention. Nevertheless, the reviewed studies also revealed several important limitations, including small sample sizes, predominantly short-term experimental designs, the absence of standardized evaluation frameworks, and unresolved ethical issues related to athlete autonomy, biometric data privacy, and algorithmic bias. Conclusion: Present the main conclusions of the research and relate them to the research objectives. Overall, the evidence suggests that HRI represents a promising approach for advancing evidence-based sports training and athlete support. Future research should prioritize longitudinal, multidisciplinary, and ethically informed investigations to evaluate the long-term effectiveness, generalizability, and practical implementation of HRI technologies across diverse sports settings.